Analysis of the Watchkeeping to Prevent Collisions on MV. Tanto Setia: Analisis Pelaksanaan Dinas Jaga untuk Mencegah Terjadinya Bahaya Tubrukan di MV. Tanto Setia - Baihaqi, Baihaqi; Laju, I Kadek; Nurmala, Eka; Dahlan, Harris R.; Hadinur, Fauzul (PT. Alpha Trianguli Australis, 2025)
Shipping is a sea transportation for transporting goods or passengers, in shipping ships, cargo ships and passenger ships are the main transportation. Collision is an emergency caused by friction between ships and each other, ships with docks, or ships with other floating objects. Ship collisions often occur due to human negligence, bad weather, and problematic navigation equipment. This study uses a qualitative approach with a descriptive method, a research strategy that aims to understand and describe phenomena in depth based on non-numerical data. The results of this study are: 1) Ship watch procedures on MV. Tanto Setia including starting from the preparation process before guarding, during guard duty, handover of guard, emergency actions while on guard, documentation during guard, adjustments for special conditions; 2) Implementation of watch duty while sailing on the MV. Tanto Setia includes initial preparation (before starting guard), during guard duty, handover of guard, emergency actions while on guard; and 3) Watch duty strategy on the MV. Tanto Setia, when an emergency occurs, includes general emergencies, collisions or risk of collision, extreme bad weather, fire, leaks or hull damage, people falling overboard (man overboard/mob), engine or steering control loss, evacuation, or major emergencies.